2016
DOI: 10.1653/024.099.sp115
|View full text |Cite
|
Sign up to set email alerts
|

Flight Activity and Mating Behavior of IrradiatedSpodoptera litura(Lepidoptera: Noctuidae) Males and Their F1Progeny for Use of Inherited Sterility in Pest Management Approaches

Abstract: The dose of radiation applied to the Oriental leafworm (also known as the common cutworm), Spodoptera litura (F.) (Lepidoptera: Noctuidae) for use in inherited sterility (IS) sterility programs must not materially reduce the quality and competitiveness of the released males. To assess the quality of sub-sterilized male moths and their F 1 progeny, their flight and mating behaviors were investigated. Thus, parental (P) generation S. litura males that had been irradiated with either 100 or 130 Gy and their F 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Furthermore, flying ability is an essential factor to be concerned in the SIT program ( Seth et al, 2016b ). According to Stephens et al (2006) , the flight ability of sterile painted apple moths was not significantly affected after being irradiated with γ-rays at 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, flying ability is an essential factor to be concerned in the SIT program ( Seth et al, 2016b ). According to Stephens et al (2006) , the flight ability of sterile painted apple moths was not significantly affected after being irradiated with γ-rays at 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, populations for genetic sex separation (GSS) from released insects should be developed before SIT technology can be used on a large scale, such as C. capitata, Bombyx mori, P. gossypiella (Peloquin et al, 2000;Tamura et al, 2000;Sahara et al, 2003;Augustinos et al, 2017). Furthermore, flying ability is an essential factor to be concerned in the SIT program (Seth et al, 2016b). According to Stephens et al (2006), the flight ability of sterile painted apple moths was not significantly affected after being irradiated with γ-rays at 100 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, sperm from successive matings in L. botrana did not compete in a random manner, but the sperm transferred during the most recent mating was predominately utilized to fertilize the eggs. Complete last-male sperm precedence was found in many economic lepidopteran species, including Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae), Spodoptera litura (F.) (Lepidoptera: Noctuidae), and P. operculella [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Complete last-male sperm precedence was found in many economic lepidopteran species, including Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae), Spodoptera litura (F.) (Lepidoptera: Noctuidae), and P . operculella [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on sperm use patterns in Oriental leafworm males revealed the precedence of sperm of the last male to mate; also their mating success, remating propensity and fertility were significantly influenced by mating sequences that included irradiated males (Seth et al 2016b, in this special issue). Thus the age of the female at her first mating with an F 1 male influenced her fertility.…”
Section: Flight Ability Of Sterile Insectsmentioning
confidence: 92%